2006
DOI: 10.1002/med.20082
|View full text |Cite
|
Sign up to set email alerts
|

Plasmepsins as potential targets for new antimalarial therapy

Abstract: Malaria is one of the major diseases in the world. Due to the rapid spread of parasite resistance to available antimalarial drugs there is an urgent need for new antimalarials with novel mechanisms of action. Several promising targets for drug intervention have been revealed in recent years. This review addresses the parasitic aspartic proteases termed plasmepsins (Plms) that are involved in the hemoglobin catabolism that occurs during the erythrocytic stage of the malarial parasite life cycle. Four Plasmodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 159 publications
2
93
0
1
Order By: Relevance
“…Plasmepsin III is one of the 10 plasmepsins coded in the P. falciparum genome and the protein is located in the food vacuole. Thus, it has been proposed as a potential anti-malarial therapeutic target (32). Upregulation of this protein by mefloquine suggests increased hemoglobin degradation, which agrees with the known mode of action of the drug.…”
Section: Effect Of Mefloquine On Plasmodium Falciparum Protein Profilesupporting
confidence: 56%
“…Plasmepsin III is one of the 10 plasmepsins coded in the P. falciparum genome and the protein is located in the food vacuole. Thus, it has been proposed as a potential anti-malarial therapeutic target (32). Upregulation of this protein by mefloquine suggests increased hemoglobin degradation, which agrees with the known mode of action of the drug.…”
Section: Effect Of Mefloquine On Plasmodium Falciparum Protein Profilesupporting
confidence: 56%
“…Individual data points are shown by crosses. Numbering of inhibitors is as in [3]. Note that the numbers of the known inhibitors are not in boldface to distinguish them from those discovered in this study.…”
Section: Enzymatic Assaymentioning
confidence: 99%
“…Inhibitors of PMs are fatal to the parasites [3], which indicates that PMs are relevant drug targets (see Ref [3] for a comprehensive list of known PM II inhibitors). Furthermore, several small-molecule inhibitors of retroviral and human aspartic proteases, namely HIV-protease [4] and renin [5], are effective and safe medicines, which provides additional support to the relevance of PMs as drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…13,18,19 However, knockout experiments have shown that the DV plasmepsins and falcipains 2 and 2′ are individually not essential to parasite survival, and because of this redundancy between the function of these enzyme classes it has proved difficult to develop drugs that effectively block the digestive process within the DV. [21][22][23][24] Peptides produced in the DV may be further processed to dipeptides by a dipeptidyl aminopeptidase I, an orthologue of mammalian cathepsin C. 25,26 Small peptides and dipeptides may also be reduced to free aminoacids within the DV and/or transported to the parasite cytosol for processing by aminopeptidases. 20,[27][28][29][30][31][32][33] Aminopeptidases are essential in releasing aminoacids from haemoglobin-derived peptides and are thus central to the growth and development of malaria parasites in the erythrocyte.…”
Section: -16mentioning
confidence: 99%